Learning by playing strategy and its role in stimulating the motivation to learn English among the first three grades - Al-Zoubi, Nour Ali Awwad (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the role of learning by playing strategy in stimulating learning motivation in its dimensions (alertness, task accomplishment, broad-mindedness) among students of the first three grades of Yazidi Mixed Secondary School. The study used the experimental approach to study the effect of the independent variable (learning by playing strategy) on the dependent variable (stimulating learning motivation), by dividing the study sample into two control and experimental groups, and the researcher designed a special scale and two pre and post-tests to measure the role of the learning strategy by playing on stimulating learning motivation. Among the most important findings of the study is the presence of statistically significant differences in the mean score of students in the dimensions of learning motivation (alertness, the accomplishment of tasks, broad-mindedness) of the experimental group in the pre and post scale in favor of the post scale. The study also found that there are statistically significant differences in the average score of students in the dimensions of learning motivation (alertness, task accomplishment, broad-mindedness) between the experimental and control groups in the pre-scale. Finally: The study found that there are statistically significant differences in the average scores of students in the dimensions of learning motivation (alertness, task accomplishment, broad-mindedness) between the experimental and control groups in the dimensional scale.